User Experience Analysis of ShopeeFood Service Using Google's HEART Framework - Oktarina, Felicia; Handoyo, Emanuel Ristian; Rahayu, Flourensia Sapty (Teknika, 2025)
The proliferation of online food delivery services has intensified the importance of user experience (UX) in determining business success. Since its launch in Indonesia in 2021, ShopeeFood, integrated within the Shopee application, has been competing with established players like GoFood, necessitating a comprehensive understanding of its user experience factors. This study employed Google's HEART Framework to evaluate the user experience of ShopeeFood through a goals-signals-metrics process, encompassing five key variables: Happiness, Engagement, Adoption, Retention, and Task Success. A mixed-method approach was implemented, combining quantitative data collection through questionnaires (n=100) with qualitative insights from user interviews, establishing a minimum target threshold of 70% for each measured variable. Statistical analysis revealed that most HEART variables demonstrated mean values falling within the "high" to "very high" categories; however, a notable exception was observed in the Retention variable, which failed to meet the predetermined minimum threshold of 70%. The findings indicate positive user reception of ShopeeFood across multiple experience dimensions, while highlighting specific challenges in user retention. To address these challenges, the study suggests implementing targeted retention strategies such as loyalty programs and enhanced user engagement initiatives. These strategies aim to transition users from promotion-driven engagement to value-based loyalty, thereby improving long-term user retention and solidifying ShopeeFood's competitive position in the market.